Analisis Kimia dan Uji Organoletik Selai Rumput Laut Euchema Spinosum - Damopolii, Niki Sirwanto; Kaseger, Bertie; Damongilala, Lena; Onibala, Hens; Pandey, Engel; Makapedua, Daisy; Sanger, Grace (Media Teknologi Hasil Perikanan, 2021)
Eucheuma spinosum as a quality processed product that has added value. Jam is an ingredient with a gel or semi-gel consistency that is made from the pulp of the fruit. The gel or semi-gel consistency in jam is obtained from the interaction of pectin compounds derived from fruit or pectin added from outside, sucrose and acid sugars. This study aims to analyze the chemistry, including water content test, ash content test, and crude fiber test and organoleptic test for seaweed Eucheuma spinosum jam. In chemical analysis tests and organoleptic tests of Eucheuma spinosum seaweed jam, the water content in Euchema spinosum seaweed jam obtained the lowest results (A2B3), which was 29.75% while the largest (A2B2) was 34.50%, the ash content In Euchema spinosum seaweed jam got the greatest result from treatment (A1B3) by 1%, the crude fiber content in Euchema spinosum seaweed jam got the greatest result in treatment (A2B2 and A2B3) which was 0.015% and the lowest (A1B2) which was equal to 0 , 05%, the Organoleptic Test for the highest appearance test was found in A1B1 with a mean value of 8.69, A2B2 taste with a mean value of 8.44, A1B3 aroma with a mean value of 8.00 and treatment of 150 gr sugar - 0 ml, and A1B1 texture with a value Average 8.56. Eucheuma spinosum sebagai suatu produk olahan yang bermutu dan memiliki nilai tambah. Selai adalah bahan dengan konsistensi gel atau semi gel yang dibuat dari bubur buah. Konsistensi gel atau semi gel pada selai diperoleh dari interaksi senyawa pektin yang berasal dari buah atau pektin yang ditambahkan dari luar, gula sukrosa dan asam. Penelitian ini bertujuan untuk menganalisis kimia yang diantaranya uji kadar air, uji kadar abu, dan uji serat kasar dan uji organoleptik selai rumput laut eucheuma spinosum. Dalam pegujian analisis kimia dan uji organoleptik selai rumput laut eucheuma spinosum di dapatkan hasil kadar air pada selai rumput laut Euchema spinosum mendapatkan hasil terendah (A2B3) yaitu sebesar 29,75% sedangkan yang terbesar (A2B2) yaitu sebesar 34,50%, Kadar abu pada selai rumput laut Euchema spinosum mendapatkan hasil terbesar dari perlakuan (A1B3) sebesar 1%, Kadar serat kasar pada selai rumput laut Euchema spinosum mendapatkan hasil paling besar pada perlakuan (A2B2 dan A2B3) yaitu sebesar 0,015% dan terendah (A1B2) yaitu sebesar 0,05%, Uji Organoleptik untuk uji kenampakan tertinggi terdapat pada A1B1 dengan nilai rerata sebesar 8,69 , rasa A2B2 dengan nilai rerata 8,44 , aroma A1B3 dengan nilai rerata 8.00 dan perlakuan 150 gr gula – 0 ml, dan tekstur A1B1 dengan nilai rerata 8.56.